Proposta de modelo de maturidade Lean Quality para construtoras - Rodegheri, Priscila Mirapalhete (2021)
The Brazilian construction industry has been intensifying the adoption of management systems based on quality. It has advanced in studying its processes in search of improved productivity, delivering higher-value products to its customers. In addition to the quality management system, construction companies have adopted Lean Construction (LC) to achieve high performance through a focus on the value expected by the customer. Linking these two management strategies, quality, and LC, emerge the Lean Quality (LQ) approach, highlighting a focus on quality management, understanding customer value expectations, and pursuing perfection. The LQ is a management strategy associated with the organizational culture and, to achieve its adoption goals, it is essential to measure the maturity of this strategy. Therefore, this research purpose a model for maturity diagnoses for LQ in Brazilian construction companies. For this, the Design Science Research (DSR) research strategy was adopted, conducting a literature review, developing, implementing, and evaluating the purposed artifact of maturity assessment, named Lean Quality Maturity Model (LQMM). This artifact has been tested in two construction companies, and its contribution to the companies was evaluated based on the participants' perceptions. This research purposes an LQ dimensions for Brazilian construction as a theoretical research outcome. The LQMM is recognized as a valid artifact from the results, and it consistently demonstrates the company's LQ maturity. Furthermore, the LQ dimensions purposed indicate to be coherent with the Brazilian construction context.